PERISTILAHAN DALAM UPACARA ANTAR AJONG MELAYU SAMBAS - Rahmadhanti, Jumiatin Asri; Saman, Sisilya; Hanye, Paternus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is aimed to describe terminology in cerasa Melayu Sambas ceremony. The method used in this research is descriptive method with qualitative research form. Sources of data in this study is a term spoken by native speakers of the village community Arung Parak. The data in this study are the words that contain the terms in the ceremony between Ajong Melayu Sambas. The technique used in this research is the technique of simak and capability which has basic technique in the form of fishing to informant who is native speaker. Based on the results of existing data analysis, it can be concluded that there are Â 25 terminology in inter ajong ceremony of sambas in the form of tool, 22 terminology in ceremony between ajong Melayu sambas in the form of materials, 9 terminology between ajong Melayu sambas form process, 8 terminology in ceremony of inter ajong Melayu sambas in the form of time, 4 terminology in ceremony between ajong Melayu sambas in the form of person who perform, and 4 terminations in ceremony between ajong Melayu sambas in the form of ritual place, there are 72 lexical meaning, and there are 51 cultural meanings.Keywords: Terminology, Inter-Ajong Ceremony, MeaningÂ